Improvement of the energy conversion efficiency of Chlorella pyrenoidosa biomass by a three-stage process comprising dark fermentation, photofermentation, and methanogenesis - Xia, A.; Cheng, J.; Ding, L.; Lin, R.; Huang, R.; Zhou, J.; Cen, K.
The effects of pre-treatment methods on saccharification and hydrogen fermentation of Chlorella pyrenoidosa biomass were investigated. When raw biomass and biomass pre-treated by steam heating, by microwave heating, and by ultrasonication were used as feedstock, the hydrogen yields were only 8.8-12.7 ml/g total volatile solids (TVS)during dark fermentation. When biomass was pre-treated by steam heating with diluted acid and by microwave heating with diluted acid, the dark hydrogen yields significantly increased to 75.6 ml/g TVS and 83.3 ml/g TVS, respectively. Steam heating with diluted acid is the preferred pre-treatment method of C. pyrenoidosa biomass to improve hydrogen yield during dark fermentation and photofermentation, which is followed by methanogenesis to increase energy conversion efficiency (ECE). A total hydrogen yield of 198.3 ml/g TVS and a methane yield of 186.2 ml/g TVS corresponding to an overall ECE of 34.0 percent were obtained through the three-stage process (dark fermentation, photofermentation, and methanogenesis).
Keywords: CHLORELLA PYRENOIDOSA; HYDROGEN; FERMENTATION; METHANOGENESIS; ENERGY CONVERSION EFFICIENCY